Rasionalitas dalam Ekonomi Islam - Muhammad Ngasifudin (JESI (Jurnal Ekonomi Syariah Indonesia), 2017)
Islamic world view of the economy is based on a paradigm that justifies the social economy as its objectivity foundaton, by positioning the race on pole position than individual interests (self interest). according to the view of conventional economic, this case is extremely irriational and does not meet the requirements of transitivity. while the islamic economic rationality can be known on the principles of islamic economics and the basic principles of the system which can be owned.